Health and economic impact of seasonal influenza mass vaccination strategies in European settings: A mathematical modelling and cost-effectiveness analysis. Issue 9 (23rd February 2022) - Sandmann, Frank G.; van Leeuwen, Edwin; Bernard-Stoecklin, Sibylle; Casado, Itziar; Castilla, Jesús; Domegan, Lisa; Gherasim, Alin; Hooiveld, Mariëtte; Kislaya, Irina; Larrauri, Amparo; Levy-Bruhl, Daniel; Machado, Ausenda; et al.
Highlights: Seasonal influenza vaccine programmes usually target at-risk and older individuals. We used an age-structured dynamic-transmission model for eight European settings. Older people benefit from adjuvanted or high-dose trivalent or quadrivalent vaccines. Adopting mass paediatric influenza vaccination is also likely to be cost-effective. Results rest on vaccine costs, willingness to vaccinate and unknown long-term effects. Abstract: Introduction: Despite seasonal influenza vaccination programmes in most countries targeting individuals aged ≥ 65 (or ≥ 55) years and high risk-groups, significant disease burden remains. We explored the impact and cost-effectiveness of 27 vaccination programmes targeting the elderly and/or children in eight European settings (n = 205.8 million). Methods: We used an age-structured dynamic-transmission model to infer age- and (sub-)type-specific seasonal influenza virus infections calibrated to England, France, Ireland, Navarra, The Netherlands, Portugal, Scotland, and Spain between 2010/11 and 2017/18. The base-case vaccination scenario consisted of non-adjuvanted, non-high dose trivalent vaccines (TV) and no universal paediatric vaccination. We explored i) moving the elderly to "improved" (i.e., adjuvanted or high-dose) trivalent vaccines (iTV) or non-adjuvanted non-high-dose quadrivalent vaccines (QV); ii) adopting mass paediatric vaccination with TV or QV; and iii) combining the elderly and paediatric strategies. We estimated setting-specific costs and quality-adjusted life years (QALYs) gained from the healthcare perspective, and discounted QALYs at 3.0%. Results: In the elderly, the estimated numbers of infection per 100, 000 population are reduced by a median of 261.5 (range across settings: 154.4, 475.7) when moving the elderly to iTV and by 150.8 (77.6, 262.3) when moving them to QV. Through indirect protection, adopting mass paediatric programmes with 25% uptake achieves similar reductions in the elderly of 233.6 using TV (range: 58.9, 425.6) or 266.5 using QV (65.7, 477.9), with substantial health gains from averted infections across ages. At €35, 000/QALY gained, moving the elderly to iTV plus adopting mass paediatric QV programmes provides the highest mean net benefits and probabilities of being cost-effective in all settings and paediatric coverage levels. Conclusion: Given the direct and indirect protection, and depending on the vaccine prices, model results support a combination of having moved the elderly to an improved vaccine and adopting universal paediatric vaccination programmes across the European settings.